STRATEGI KEPEMIMPINAN SEKOLAH DAN PENGEMBANGAN PROFESIONALISME GURU DI ERA DIGITAL MENDUKUNG INTEGRASI TEKNOLOGI DALAM PENDIDIKAN - Samosir, Esther Naomi; Turan, Septi Indrawani; Komariyah, Laili (Jurnal Pengabdian Kreativitas Pendidikan Mahakam (JPKPM), 2024)
ABSTRACT In the era of digitalization, effective school leadership and teacher professionalism development are crucial for successful integration of technology in education. This research aims to explore the strategies of school leadership and the development of teacher professionalism in the digital era. Using a qualitative approach, data were collected through interviews and observations from 10 teachers and 2 school leaders. The findings reveal that clear vision and strategic planning by school leaders are essential in guiding schools towards effective technology integration. Training and ongoing professional development for teachers play a significant role in enhancing their technological skills and innovative teaching practices. Collaboration among teachers and adequate technical support are also crucial factors in promoting effective technology use in education. The study contributes to a deeper understanding of how school leadership and teacher professionalism influence learning effectiveness in the digital age. Keywords: School leadership, teacher professionalism, digital era, technology integration, educational effectiveness.